NUTRIENT WASTE LOAD FROM VANAME SHRIMP (Litopeneaus vannamei) AND ANALYSIS OF LAND SUITABILITY BASED ON WATER QUALITY CRITERIA IN EARTH IN EAST RAWAJITU PROSPEROUS - R Aken Yugo; Eko Effendi; Herman Yulianto (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2020)
Bumi Dipasena Sejahtera as part of Bumi Dipasena, which is managed by PT. Dipasena Citra Darmaja is the largest shrimp farming in Southeast Asia. Since operating in 1980, Bumi Dipasena has made production up to 200 tons/day. However, the current condition shows a decrease in total production to 30 – 40 tons/day from 16.000 operated ponds. Decreasing production is caused by declining water quality. This study aims to find out about nutrient loading and water suitability based on water quality criteria. Nutrient loading is determined from total production calculated from three different ponds. Suitability analysis was conducted by matching and scoring methods based on water quality measured at 7 sites in the inlet, outlet, and pond site. The result shows that nutrient loading has the highest value at the highest production. Water suitability analysis both of inlet and ponds include in suit marginal class (S3).